PERAN ELIT LOKAL DALAM KEMENANGAN PARTAI GERINDRA PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2014 DI KABUPATEN LUWU UTARA - Iqbal Aidar Idrus; Titin Purwaningsih (Universitas Muhammadiyah Yogyakarta, 2016)
Gerindra Partybecome participants first general election in 2014, followed by twelve Parties. Although first-time election in Luwu North,Gerindra Party succeeded in gaining the most votes to two after the Golkar Party and get a ration of six seats to the council. This success is supported by community leaders in Luwu North who come from the elite, like the elite bureaucrats, the economic elite (businessmen),and the political elite have major stakes in attracting community investigator to choose legislative candidates coming fromGerindra Party. Therefore, the role of the local elite in winning Gerindra be the focus of study in this research.This study used qualitative methods, with data collection techniques are in-depth interviews and documentation. As the informants in this study, namely, the Chairman of DPC Gerindra, six legislators from Gerindra, community leader and Vice Regent of Luwu North.The results of this study indicate that the role of local elites on the award Gerindra using three approaches, namely positional approach to reputation and approach decision,Where the outcome of the vote Gerindra 6.5%, 39.2% of elected candidates sound, the sound of a candidate not elected 54.3% of all candidates who have as many as thirty-five candidates,so Gerindra managed to gain six seats to sit in Parliament Luwu north. In general, people in North Luwu choose legislators opted for track record is not actor or party,but because it is based on the election of community leaders who attended, besides the factor of emotional closeness, kinship and familiarity with community leaders.